A influência da imprensa no processo de ampliação da transparência no TCE-RS - Oliveira, Priscila Pinto de (2012)
This dissertation analyses the media influence on introduction of transparency processes at Tribunal de Contas do Estado do Rio Grande do Sul (TCE-RS) between 2008 and 2011. In order to achieve this purpose, first we present the concepts of public transparency and accountability according the literature. The focus is to show how the media acts as an agent of social responsiveness. After, we expose the political context and the institutional changes that occurred at TCE-RS during the period in analyses. The media view of this time is also focused. The objective is to show the context of the decision making moments regarding transparency. Then, we analyses four interviews made with the men who were president of TCE-RS during the period in focus. The interview intent is to reveal factors that influenced the introduction of transparency processes at TCE-RS. Our findings indicate that media played a key role at these institutional changes.